Receipt of mRNA COVID-19 vaccines preconception and during pregnancy and risk of self-reported spontaneous abortions, CDC v-safe COVID-19 Vaccine Pregnancy Registry 2020-21 - Zauche L; Wallace B; Smoots A; Olson C; Oduyebo T; Kim S; Peterson E; Ju J; Beauregard J; Wilcox A; Rose C; Meaney-Delman D; et al. (ResearchSquare, 2021)
Background There is continuing public concern about the safety of COVID-19 vaccination during pregnancy. While there is no compelling biological reason to expect that mRNA COVID-19 vaccination (either preconception or during pregnancy) presents a risk to pregnancy, data are limited. It is, however, well documented that SARS-CoV-2 infection during pregnancy is associated with severe illness and increased risk of adverse pregnancy outcomes. Among recognized pregnancies in high-income countries, 11–16% end in spontaneous abortion (SAB). Methods People enrolled in v-safe, a voluntary smartphone-based surveillance system, who received a COVID-19 vaccine preconception or during pregnancy were contacted by telephone to enroll in the v-safe pregnancy registry. V-safe pregnancy registry participants who received at least one dose of an mRNA COVID-19 vaccine preconception or prior to 20 weeks’ gestation and who did not report a pregnancy loss before 6 completed weeks’ gestation were included in this analysis to assess the cumulative risk of SAB using Life Table methods. Results Among 2,456 pregnant persons who received an mRNA COVID-19 vaccine preconception or prior to 20 weeks’ gestation, the cumulative risk of SAB from 6–19 weeks’ gestation was 14.1% (95% CI: 12.1, 16.1%). Using direct age standardization to the selected reference population, the age-standardized cumulative risk of SAB was 12.8% (95% CI: 10.8–14.8%). Conclusions When compared to the expected range of SABs in recognized pregnancies, these data suggest receipt of an mRNA COVID-19 vaccine preconception or during pregnancy is not associated with an increased risk of SAB. These findings add to accumulating evidence that mRNA COVID-19 vaccines during pregnancy are safe.